Importance of NT-proBNP and conventional risk factors for prediction of death in older adults with and without diabetes mellitus– A report from the Atherosclerosis Risk in Communities (ARIC) study. (December 2022) - Wijkman, Magnus O.; Claggett, Brian L.; Malachias, Marcus V.B.; Vaduganathan, Muthiah; Ballantyne, Christie M.; Kitzman, Dalane W.; Mosley, Thomas; Matsushita, Kunihiro; Solomon, Scott D.; Pfeffer, Marc A.
Highlights: NT-proBNP as a single biomarker predicted all-cause death in older adults. In those without diabetes, NT-proBNP discriminated similarly as the PCE variables. In those with diabetes, NT-proBNP discriminated better than the PCE variables. Abstract: In this community-based cohort of 5861 individuals followed for median 7.2 years, the discriminatory ability of NT-proBNP alone in predicting mortality was similar to that of multiple conventional markers of risk in people without diabetes. In people with diabetes, NT-proBNP alone discriminated risk of mortality better than conventional risk factors.